Intraoperative characteristic of patients with ischemic mitral insufficiency - Rudenko, S. A.; Rudenko, A. V.; Trembovetskaya, E. N.; Gogaeva, E. K.; Lazoryshynetz, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
In the past, almost all operations were performed according to the prosthetic technique, and in recent years we have begun to differentiate our approach to the choice of methods for the surgical correction of mitral insufficiency of ischemic genesis. Patients were divided into two groups depending on the surgical treatment tactics. The first group included patients who underwent plastic surgery on the valves. Prosthetic mitral valve was performed in patients of the second group. The duration of aortic occlusion is also quite significantly different in both groups. In the first group, it was 98.8±29.2 min., whereas in the second – 115.8±33.2 min. On the one hand, this can be explained by the large amount of work that was performed during mitral valve replacement. It is understood that sometimes prosthetics were preceded by attempts to per-form plastic surgery. The number of distal anastomoses was determined by the number of affected coronary arteries. In 108 (76.1%) patients, mitral valve repair was the method of choice for the correction of mitral insufficiency. However, during the revision and study of the results in the intraoperative period, 15 (13.9%) performed the valve-preserving operation as not being sufficiently successful. In these cases, it was decided to perform a prosthetic mitral valve. Of all 49 mitral valve prosthetics, only 34 (69.4%) patients decided to perform an operation using this method from the very beginning. And for 15 (30.6%) patients, valve prosthetics became the method of choice after unsuccessful mitral plasty.